HFpEF etiology – Can focus on sex-specific mechanisms deliver insights for all? - Delbridge, L.M.D.; Bell, J.R.; Weeks, K.L.; Raaijmakers, A.J.A.; Mellor, K.M. (Journal of molecular and cellular cardiology, 2022)
[Display omitted] •HFpEF is highly prevalent in women, with a gender distribution ratio of 2:1.•The aging female demographic confers an increased burden of disease in women.•Women with HFpEF have markedly increased incidence of diastolic dysfunction.•Sex-specific molecular understanding of diastolic dysfunction in HFpEF is required.•Discerning the mechanisms of HFpEF sex disparity will help identify new treatments.